2010
DOI: 10.1038/nmat2778
|View full text |Cite
|
Sign up to set email alerts
|

A self-assembly pathway to aligned monodomain gels

Abstract: Aggregates of charged amphiphilic molecules have been found to access a structure at elevated temperature that templates alignment of supramolecular fibrils over macroscopic scales. The thermal pathway leads to a lamellar plaque structure with fibrous texture that breaks upon cooling into large arrays of aligned nanoscale fibres and forms a strongly birefringent liquid. By manually dragging this liquid crystal from a pipette onto salty media, it is possible to extend this alignment over centimetres in noodle-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
614
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 588 publications
(625 citation statements)
references
References 34 publications
9
614
2
Order By: Relevance
“…Their data suggested that the local packing was not changed by heating and cooling, but that the aggregates were dehydrated by heating, leading to filaments with significantly greater diameters. This increase in diameter was backed up by changes in the SAXS data 16. Hence, our systems are behaving differently.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Their data suggested that the local packing was not changed by heating and cooling, but that the aggregates were dehydrated by heating, leading to filaments with significantly greater diameters. This increase in diameter was backed up by changes in the SAXS data 16. Hence, our systems are behaving differently.…”
mentioning
confidence: 84%
“…with respect to peptide amphiphiles,16 where heating and cooling led to a change in the properties of the solution and greater alignment of structures. The heating and cooling was found to be necessary to allow “noodling”, for example.…”
mentioning
confidence: 99%
“…For example, the solution viscosity increased significantly. 93 The gel that was formed on addition of a calcium salt was also significantly stiffer than when the salt was added to a solution that had not been heated and cooled before the addition of the salt. The increased viscosity also allowed ''noodles'' to be drawn out.…”
Section: Process Of Assemblymentioning
confidence: 99%
“…example, are synthetic molecules that can self-assemble into nanofibres and create functional 3D hydrogels that emulate the fibrous architecture of the extracellular matrix (ECM) 11,12 . Nonetheless, most peptide and/or protein materials are formed through equilibrium-based self-assembly approaches that are capable of generating stable supramolecular structures, but with limited hierarchy and spatiotemporal control, which has hindered their functionality 2 .…”
mentioning
confidence: 99%